2015
DOI: 10.1016/j.jamda.2015.01.088
|View full text |Cite
|
Sign up to set email alerts
|

Frailty as a Predictor of the Incidence and Course of Depressed Mood

Abstract: Background Late-life depression and physical frailty are supposed to be reciprocally associated, however, longitudinal studies are lacking. Objectives This study examines whether physical frailty predicts a higher incidence of depression, as well as a less favorable course of depression. Methods A population-based cohort study of 888 people aged 65 years and over with follow-up measures at 3, 6, and 9 years. Cox proportional hazards models adjusted for age, sex, education, smoking, alcohol usage, and globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
66
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 51 publications
7
66
1
4
Order By: Relevance
“…In a study with health professionals regarding criteria to indicate frailty, it was noted that there were no uniformly determined criteria among such individuals, and that the data obtained was prone to subjectivity 17 , diverging from the most cited definitions in international literature 1,[18][19][20][21] . The use of the application can help in the identification of parameters for the evaluation of frailty, to reach a consensual and homogeneous definition.…”
Section: Agrigoroaei and Lachmanmentioning
confidence: 99%
“…In a study with health professionals regarding criteria to indicate frailty, it was noted that there were no uniformly determined criteria among such individuals, and that the data obtained was prone to subjectivity 17 , diverging from the most cited definitions in international literature 1,[18][19][20][21] . The use of the application can help in the identification of parameters for the evaluation of frailty, to reach a consensual and homogeneous definition.…”
Section: Agrigoroaei and Lachmanmentioning
confidence: 99%
“…12,17 Furthermore, recent studies have shown that frailty may be related to mood change, 16,18 although the nature of this association, as well as its relevance to the frailty construct, needs to be clarified. 17 Regarding the prevalence of frailty, systematic comparison of numerous studies 19 shows that frailty in community-dwelling adults aged 65 and over varies from 4% to 17%.…”
Section: Introductionmentioning
confidence: 99%
“…70,71 Frailty is a predictor of depression. 72,73 This may be due to increased peripheral cytokines playing a role in the pathophysiology of depression. 74 Diabetes is associated with depression, falls, cognitive impairment, frailty, and gait instability.…”
mentioning
confidence: 99%